2017
DOI: 10.3389/fnins.2017.00249
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Test-Retest Reliability of Resting State fMRI by Removing the Impact of Sleep

Abstract: Resting state functional magnetic resonance imaging (rs-fMRI) provides a powerful tool to examine large-scale neural networks in the human brain and their disturbances in neuropsychiatric disorders. Thanks to its low demand and high tolerance, resting state paradigms can be easily acquired from clinical population. However, due to the unconstrained nature, resting state paradigm is associated with excessive head movement and proneness to sleep. Consequently, the test-retest reliability of rs-fMRI measures is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 100 publications
(180 reference statements)
7
23
0
1
Order By: Relevance
“…The variability in the EC condition may be greater as a result of participants being in a more drowsy state or to the fact that its less controlled nature may lead to more mind wandering. Of note, Wang, Han, Nguyen, Guo, and Guo () reached higher reliability of FC by removing volumes with high sleepiness, and Patriat et al (); Zou et al () reported higher test–retest reliability in EO or EO‐F conditions compared to EC. In addition to that, (Allen et al, ) reported that according to EEG data; subjects are more likely to get into drowsy/early‐sleep states during EC comparing to EO condition.…”
Section: Discussionmentioning
confidence: 95%
“…The variability in the EC condition may be greater as a result of participants being in a more drowsy state or to the fact that its less controlled nature may lead to more mind wandering. Of note, Wang, Han, Nguyen, Guo, and Guo () reached higher reliability of FC by removing volumes with high sleepiness, and Patriat et al (); Zou et al () reported higher test–retest reliability in EO or EO‐F conditions compared to EC. In addition to that, (Allen et al, ) reported that according to EEG data; subjects are more likely to get into drowsy/early‐sleep states during EC comparing to EO condition.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, we note another important factor that limits the reliability of rsfMRI-guided target is the temporally varying cognitive states which leads to dynamic FC maps [38, 39, 40]. A suitable approach to remove the influence of different cognitive states could potentially improve the reliability of FC maps [41]. …”
Section: Discussionmentioning
confidence: 99%
“…However, such solutions do not work for studies of passive states (e.g., resting state fMRI, naturalistic viewing fMRI), as there are no such responses to monitor. The resting state fMRI literature has struggled with this issue due to the increased likelihood of individuals falling asleep (Tagliazucchi and Laufs 2014;Wang et al 2017), driving most to require participants to remain with their eyes open during scans -a requirement that can be tracked through direct observation by a technician or via video recording. The requirements of conducting fMRI movie viewing experiments are greater, as one needs to know that an individual is actually paying attention to specific information on the screen.…”
Section: Introductionmentioning
confidence: 99%